Analisis Pengembangan Kurikulum CEFR Bahasa Arab di Eropa dan Internasional - Fawzi Abdi Salam, Ahmad; Royan Firdaus, Muhammad; Amaliah, Thariqatul; Ulul Azmy, Muhammad; Hasanah, Uswatun (UIR Press, 2025)
This study aims to analyze the development of Arabic language curricula based on the Common European Framework of Reference for Languages (CEFR) in the European and international contexts using content analysis with a descriptive qualitative approach. Data were collected through a literature study of CEFR-based Arabic language curricula and related publications. The analysis included data reduction, categorization, and interpretation, with validity ensured through source triangulation and verification against official CEFR documents and related institutions. The CEFR has become a global standard in language learning, including Arabic, which is used to assess language competence objectively. This study examines policy documents, academic syllabi, and related publications to explore how CEFR principles are applied in Arabic language curricula in various countries. The results of the analysis show that the development of a CEFR-based Arabic language curriculum demonstrates progress in the standardization of Arabic language learning at the European and international levels. The CEFR provides a measurable leveling framework and encourages communicative and contextual learning. This curriculum emphasizes competence in the four language skills with descriptions of the abilities at each level. However, its implementation still faces obstacles such as limited materials, linguistic and cultural differences, and a lack of teacher training. Collaboration between institutions is needed for the effective and sustainable implementation of the CEFR.